STRATEGI PENGEMBANGAN AGRIBISNIS KOMODITI JAMBU BIJI MERAH - Livina Aisyara (SUAN PUBLISHER, 2024)
This study aims to formulate an effective and sustainable red guava commodity agribusiness development strategy in the research area. Red guava has great potential as a superior commodity because of its high nutritional content, stable market demand, and good adaptation to local climate. However, the development of its agribusiness still faces various obstacles, ranging from production, post-harvest, to marketing aspects. This study will use survey and in-depth interview methods with qualitative and quantitative descriptive approaches (SWOT and AHP analysis). Data will be collected from farmers, traders, consumers, and related stakeholders. Predictive results indicate that development strategies should focus on improving product quality, diversifying processing, strengthening farmer institutions, and increasing market access. This study is expected to provide comprehensive strategic recommendations for stakeholders to maximize the potential of red guava agribusiness.